Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.